Does disability modify the association between poor mental health and violence victimisation over adolescence? Evidence from the CoVAC cohort study in Uganda. - Daniel J Carter; Charlie F M Pitcairn; Emily Eldred; Louise Knight; Janet Nakuti; Angel Mirembe; Lydia Atuhaire; Elizabeth Allen; Amiya Bhatia; Dipak Naker; Jenny Parkes; Karen Devries (PLOS Global Public Health)
We aimed to estimate the impact of poor mental health in early adolescence on subsequent poor mental health, depression, and violence victimisation in late adolescence and to determine whether young people living with disabilities experienced a stronger relationship between mental health and these outcomes. Data from two waves of a longitudinal cohort study of 2773 Ugandan adolescents were used to assess the impact of mental health difficulties in early adolescence (aged 11-14) on presence of subsequent mental health difficulties, depression and past year violence victimisation in later adolescence (aged 15-18). We used g-computation to examine how these outcomes changed dependent on levels of poor mental health in early adolescence and explored functional difficulties as an effect modifier. This study demonstrates high prevalence of mental health difficulties in adolescence. There is a positive association between mental health difficulties in early adolescence and experience of mental health difficulties, depression, and past year violence in later adolescence. The risk of poor outcomes is greater for individuals experiencing poorer mental health in early adolescence. The relationships between early mental health difficulties and both mental health difficulties in later adolescence and past year violence are stronger in young people with functional difficulties. Poor mental health in early adolescence is associated with depression and violence victimisation in later adolescence, and the association is stronger among adolescents living with disabilities. School-aged adolescents would benefit from violence prevention and mental health promotion interventions which are inclusive and engage and respond to the needs and rights of adolescents with disabilities.